Cholera: Immunity and Prospects in Vaccine Development. (1st September 2018) - Harris, Jason B
Abstract: Vibrio cholerae is a prototypical noninvasive mucosal pathogen, yet infection generates long-lasting protection against subsequent disease. Vibriocidal antibody responses are an imperfect but established correlate of protection against cholera following both infection and vaccination. However, vibriocidal antibody responses are likely a surrogate marker for longer-lasting functional immune responses that target the O-polysaccharide antigen at the mucosal surface. While the current bivalent inactivated oral whole cell vaccine is being increasingly used to prevent cholera in areas where the disease is a threat, the most significant limitation of this vaccine is it offers relatively limited direct protection in young children. Future strategies for cholera vaccination include the development of cholera conjugate vaccines and the further development of live attenuated vaccines. Ultimately, the goal of a multivalent vaccine for cholera and other childhood enteric infections that can be incorporated into a standard immunization schedule should be realized.